2013
DOI: 10.1038/ncb2783
|View full text |Cite
|
Sign up to set email alerts
|

The Lin28b–let-7–Hmga2 axis determines the higher self-renewal potential of fetal haematopoietic stem cells

Abstract: Mouse haematopoietic stem cells (HSCs) undergo a postnatal transition in several properties, including a marked reduction in their self-renewal activity. We now show that the developmentally timed change in this key function of HSCs is associated with their decreased expression of Lin28b and an accompanying increase in their let-7 microRNA levels. Lentivirus-mediated overexpression of Lin28 in adult HSCs elevates their self-renewal activity in transplanted irradiated hosts, as does overexpression of Hmga2, a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
352
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(366 citation statements)
references
References 58 publications
12
352
2
Order By: Relevance
“…Inhibition of LIN-28B promotes the maturation of let-7, thereby leading to the translation reduction of let-7a targets such as c-MYC and RAS, and the decreased tumorigenesis [9]. In addition, the critical role of LIN-28B/let-7 axis has been demonstrated in programing and maintaining stem cells [10,11], as well as in promoting epithelial-mesenchymal transition (EMT) [12], tumorigenesis and metastasis [11]. The involvement of the LIN-28B/let-7 axis in cancer has also been studied in vivo neuroblastoma animal model; LIN-28B overexpression-induced neuroblastma had markedly low levels of let-7 miRNA and high levels of MYC protein [13].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of LIN-28B promotes the maturation of let-7, thereby leading to the translation reduction of let-7a targets such as c-MYC and RAS, and the decreased tumorigenesis [9]. In addition, the critical role of LIN-28B/let-7 axis has been demonstrated in programing and maintaining stem cells [10,11], as well as in promoting epithelial-mesenchymal transition (EMT) [12], tumorigenesis and metastasis [11]. The involvement of the LIN-28B/let-7 axis in cancer has also been studied in vivo neuroblastoma animal model; LIN-28B overexpression-induced neuroblastma had markedly low levels of let-7 miRNA and high levels of MYC protein [13].…”
Section: Introductionmentioning
confidence: 99%
“…S1), suggested that ECCM activities regulated RPCs by recruiting disparate signaling pathways whose targets could be Hmga2 and Smarca4. Here, given its role in regulating tissue-specific stem cells, we examined the involvement of Hmga2 (Nishino et al, 2008;Copley et al, 2013). Hypothesis testing involved: (1) the examination of intercellular pathways, which necessitates that ECs express the corresponding ligands for the identified receptors in RPCs (Wang et al, 2007); and (2) determining whether the recruitment of the signaling pathway(s) engaged Hmga2 expression.…”
Section: Identification Of Hmga2 In Ec-mediated Rpcs Regulationmentioning
confidence: 99%
“…LIN-28 inhibits the biogenesis of the mature form of the let-7 microRNA (miRNA) (Newman et al, 2008;Piskounova et al, 2008;Van Wynsberghe et al, 2011;Viswanathan et al, 2008). When LIN-28 is downregulated, mature let-7 miRNA is produced, directing cells toward differentiated/adult fates (Copley et al, 2013;Hayes and Ruvkun, 2006;Rybak et al, 2008;Thornton and Gregory, 2012;Tsialikas and Romer-Seibert, 2015;Yu et al, 2007) by inhibiting the translation of primarily lin-41 and other target mRNAs (Ecsedi and Grosshans, 2013;Long et al, 2007;Slack et al, 2000;Vella et al, 2004a,b). homologs are proposed to silence the translation of target mRNAs (Ecsedi and Grosshans, 2013;Ecsedi et al, 2015;Loedige et al, 2013;Sonoda and Wharton, 2001;Vella et al, 2004a,b) that otherwise promote an undifferentiated/juvenile state (Chang et al, 2012;Ecsedi and Grosshans, 2013;Rybak et al, 2009).…”
Section: Introductionmentioning
confidence: 99%